Research Progress of Digital Social Innovation - Chen, Huizhen (International Journal of Social Sciences and Public Administration, 2024)
Digital social innovation has been rapidly emerging around the world and is attracting more and more attention. By collating and reviewing the relevant literature of digital social innovation, the current research status is summarized, and the potential research direction in the future is analyzed. It is found that the role of digital social innovation is influenced by the development level of information and communication technology, the construction level of digital infrastructure and the commitment level of digital technicians at the technical level, the size and type of organizations and the innovation ability of organizations at the organizational level, and the policy, economic and social environment at the environmental level. The role of digital social innovation in more fields, the role of social organizations and the local practice of digital social innovation are future research directions.